2013
DOI: 10.1093/ajae/aat049
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Effects of Sugar‐Sweetened Beverage Taxes on Food and Beverage Demand in a Large Demand System

Abstract: A censored Exact Affine Stone Index incomplete demand system is estimated for 23 packaged foods and beverages and a numéraire good. Instrumental variables are used to control for endogenous prices. A half-cent per ounce increase in sugar-sweetened beverage prices is predicted to reduce total calories from the 23 foods and beverages but increase sodium and fat intakes as a result of product substitution. The predicted decline in calories is larger for low-income households than for high-income households, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
297
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(323 citation statements)
references
References 35 publications
12
297
3
Order By: Relevance
“…These studies generally find no significant effects, possibly due to the low salience of sales taxes relative to excise taxes (Fletcher, Frisvold, and Tefft., 2015;Fletcher, Frisvold, and Tefft., 2010;Sturm et al, 2010;Powell, Chriqui, and Chaloupka 2009). While numerous studies estimate how a beverage tax 5 would affect consumer demand (e.g., Zhen et al, 2014), our work is relatively rare in that we exploit both cross-sectional and temporal variation in tax rates rather than merely price variation in order to identify an effect. This makes our findings more reliable and realistic than previous estimates.…”
mentioning
confidence: 99%
“…These studies generally find no significant effects, possibly due to the low salience of sales taxes relative to excise taxes (Fletcher, Frisvold, and Tefft., 2015;Fletcher, Frisvold, and Tefft., 2010;Sturm et al, 2010;Powell, Chriqui, and Chaloupka 2009). While numerous studies estimate how a beverage tax 5 would affect consumer demand (e.g., Zhen et al, 2014), our work is relatively rare in that we exploit both cross-sectional and temporal variation in tax rates rather than merely price variation in order to identify an effect. This makes our findings more reliable and realistic than previous estimates.…”
mentioning
confidence: 99%
“…For instance, two different UKbased studies showed that taxing exclusively the principal sources of dietary saturated fat may not improve health, as the benefits may be offset by an increase in salt consumption in the presence of substitute foods (Nnoaham et al, 2009;Mytton et al, 2007). Similarly, a study of the effects of taxes on SSBs predicted a potential increases in sodium and fat intake (Zhen et al, 2013).…”
mentioning
confidence: 99%
“…However, a study of people aged over 50 in the United States concluded that only modest changes in body weight can be expected in the short term, while a permanent reduction in price per calorie of 10% would generate a 1.9 body mass index reduction in the long term (Goldman et al, 2009). A further US study produced estimates of the impact on people's weight of a 0.5 to 1 cent per ounce tax on SSBs, using different demand models (Finkelstein et al, 2013;Zhen et al, 2013). The weight reduction was modest as an individual average (well below 1 kg, after one year), but this would likely translate into a non-negligible reduction in the proportion of people who are overweight or obese in the population.…”
mentioning
confidence: 99%
See 2 more Smart Citations